PENGARUH DEBT TO EQUITY RATIO (DER) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM (STUDI KASUS PADA PERUSAHAAN SUB SEKTOR PERTAMBANGAN BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2014 – 2019) - Putri Asri Budiyani; Dailibas - (Politeknik Ganesha Medan, 2020)
The development of the coal mining subsector companies have decreased, especially in stock prices. The companies performance is the main point for investors to invest in the middle of a less good level influenced by various factors, including due to debt and profit. Financial statements are a proof of the companies performance. Searching for these factors is done by analyzing financial ratios related to debt and profits. The purpose of this research is analyze whether DER and EPS have a partial and simultaneous effect on stock prices. The population are all coal mining subsector companies listed on the Indonesia Stock Exchange (BEI) in the period 2014-2019 with a sample of 10 companies. This research is quantitative with purposive sampling technique. The data used are financial statements published by the Indonesia Stock Exchange (BEI) and then processed using SPSS for Windows 25. The results of the research get that partially DER has no effect on stock prices while EPS has an effect on stock prices. Simultaneously the DER and EPS have effects together on stock prices. Based on the results of DER and EPS with regression models, the variables have a strong influence on stock prices with determination were 37%. The biggest influence was contributed is EPS by 31% and then DER by 6%.